A combined multi-criteria approach to support FMECA analyses: A real-world case. (January 2018) - Carpitella, Silvia; Certa, Antonella; Izquierdo, Joaquín; La Fata, Concetta Manuela
Highlights: Combination of FMECA and MCDM methods to optimize maintenance activities. Considering different evaluation criteria in respect to the RPN to rank failure modes. Application of FTOPSIS and AHP MCDM methods for the failure modes prioritization. Application to the real-world case study of a street cleaning vehicle. Abstract: The paper proposes an approach that combines reliability analyses and multi-criteria decision methods to optimize maintenance activities of complex systems. A failure mode, effects, and criticality analysis (FMECA) is initially performed and the fuzzy TOPSIS (FTOPSIS) method is then applied to rank previously identified failure modes. For prioritization, failure modes are assessed against three evaluation criteria that differ from those traditionally involved in risk priority number (RPN) computation (i.e. severity, occurrence and detection). Two criteria refer to the maintenance management reflecting the operational time taken by the maintenance activity performed after the occurrence of a specific fault, and the way such an action is executed. The third criterion reflects the classical frequency of the occurrence of faults. To further develop previous research, the analytic hierarchy process (AHP) is herein applied to weight evaluation criteria and a group of experts is involved with aspects associated with the considered criteria. The approach is applied to a real-world case study, showing that the obtained results represent a significant driver in planning maintenance activities. To test the influence of criteria weights on ranking results, a sensitivity analysis is carried out by varying the vector of criteria weights obtained from the group decision process.